Infolding of fenestrated endovascular stent graft - Zelt, Jason G.E. (J Vasc Surg Cases Innov Tech, 2017)
We report a case of infolding of a fenestrated stent graft involving the visceral vessel segment after a juxtarenal abdominal aorta aneurysm repair. The patient remains free of any significant endoleak, and the aortic sac has shown regression. The patient remains asymptomatic, with no abdominal pain, with normal renal function, and without ischemic limb complications. We hypothesize that significant graft oversizing (20%-30%) with asymmetric engineering of the diameter-reducing ties may have contributed to the infolding. Because of the patient's asymptomatic nature and general medical comorbidities, further intervention was deemed inappropriate as the aneurysmal sac is regressing despite the infolding.